Innovative low temperature plasma approach for deposition of alumina films - Darriba Battaglin, Felipe Augusto [UNESP]; Hosokawa, Ricardo Shindi [UNESP]; Cruz, Nilson Cristino da [UNESP]; Caseli, Luciano; Rangel, Elidiane Cipriano [UNESP]; Silva, Tiago Fiorini da; Tabacniks, Manfredo Harri (Univ Fed Sao Carlos, Dept Engenharia Materials, 2014)
Alumina films were deposited from a new plasma method using aluminum acetylacetonate (AAA) powder as precursor. The AAA was sputtered in argon and oxygen plasma mixtures. It was investigated the effect of the oxygen proportion (O-2 %) on the properties of the coatings. Deposition rate was derived from the layer height measured by profilometry. The elemental composition and molecular structure of the films were determined by Rutherford backscattering and infrared spectroscopies, respectively. Grazing incidence X-ray diffraction was used to investigate the microstructure of the films while hardness was determined by nanoindentation technique. Inspections on the surface morphology and on the film composition were conducted associating scanning electron microscopy and energy dispersive spectroscopy. Incorporation of oxygen affects the plasma kinetics and consequently the properties of the coatings. As moderated concentrations of oxygen (<25%) are added, the structure is predominantly organic containing stoichiometric amorphous alumina. On the other hand, as high O-2 % (> 25%) are incorporated, the structure become rich in metallic aluminum with carbon rising at low proportions. The deposited layer is not homogeneous in thickness once the chemical composition of the precursor is changed by the action of the reactive oxygen plasma. Oxygen ablation on the film surface also contributes to the lack of homogeneity of the structure, especially as high oxygen proportions are imposed. Hardness data (0.5-2.0 GPa) corroborated the idea of an amorphous structure. Based on the results presented here it was possible to identify the oxygen concentration in the plasma atmosphere which mostly removed organics while preserving the stoichiometric alumina precipitation, subject of great relevance as one considers the reduction in the energy necessary for the creation of fully oxide coatings.
Keywords: Alumina; Aluminum acetylacetonate; Reactive plasma sputtering; Composition; Structure; Morphology